Social Capital and Health Inequality in European Welfare States - Rostila, M. author. aut Link
XIX, 234 p.
Keywords: Drawing on cross-national European data from the European Social Survey as well as Swedish national survey data and registers, this book investigates social capital in relation to health and health inequalities in European welfare states.